Whey proteins. From supplementation to physiological modulation - Sukkar, S.G.; Derin, L.; Iorio, E.L. (Progress in Nutrition, 2011)
SummaryResults from the experimental and clinical studies started around 30 years ago due to the pioneering work of Bounous and to the parallel incredible progress made by biochemistry and food technologies, make currently available to nutritionists and health professionals in general a series of highly purified whey protein formulations – extremely similar to the native ones. Further adjustments of the production technique consisting of delactosing and elimination of fats have allowed us to achieve highly purified preparations that are also safer from an allergen point of view and also more suitable in hypolipidic diet regimens. Research continues to look for biochemical processes that are at the basis of the positive clinical effects produced by whey proteins but at least one consideration seems to emerge from the numerous past works mentioned in this first section. The acknowledgement of a series of effects linked to the dosage that is in some way proportional to body weight - correlated with the nutritional quality of the raw material that is the source of the macromolecules indispensable for anabolic processes – should be accompanied by others, linked to the intake of more modest quantities – likely related to a particular aminoacid composition or, in any case, to small peptide sequences – compatible with the modulation of important cell functions, including the control of the oxidative balance mediated by the synthesis of endogenous glutathione.Le proteine da siero di latte. Dall’integrazione nutrizionale alla modulazione fisiologicaRiassuntoI risultati degli studi sperimentali e clinici iniziati circa 30 anni fa grazie all’opera pionieristica di Bounous da una parte ed i passi da gigante compiuti, in parallelo, dalla biochimica e dalle tecnologie alimentari rendono oggi disponibili al nutrizionista ed ai professionisti della salute in genere formulazioni altamente purificate – in condizioni molto simili a quelle native – di proteine da siero di latte. Ulteriori affinamenti della tecnica di produzione, attraverso l’allontanamento del lattosio e dei grassi, consentono di ottenere, accanto all’elevata resa, preparati sempre più sicuri sotto il profilo dell’allergenità e, rispettivamente, maneggevoli, anche in regimi dietetici ipolipidici. La ricerca è continuamente impegnata a dare un volto ai processi biochimici che sono alla base dei favorevoli riscontri clinici esibiti dalle proteine da siero di latte ma almeno una considerazione sembra emergere dai molteplici lavori passati in rassegna in questa prima sezione. Accanto ad una serie di effetti legati ad un dosaggio in qualche modo proporzionale al peso corporeo – correlati con la qualità nutrizionale della materia prima quale fonte di macromolecole indispensabili per i processi anabolici – bisogna riconoscerne altri, legati all’assunzione di più modeste quantità – verosimilmente correlati con la particolare composizione amminoacidica o, comunque, a piccole sequenze peptidiche – compatibili con la modulazione di importanti funzioni cellulari, tra cui il controllo del bilancio ossidativo attraverso la sintesi endogena di glutatione